Porcine Lactic Dehydrogenase in the Serum of Patients Treated by Extracorporeal Porcine Liver Perfusion. Issue 5649 (12th April 1969) - Bersohn, I.; Kew, M. C.; Rolle, M.; Mieny, C. J.; Myburgh, J. A.
Abstract : Porcine lactic dehydrogenase (L.D.H.) has been found in the serum of four patients in hepatic coma treated by extracorporeal porcine liver perfusion. A comparison between the porcine L.D.H. isoenzyme pattern in the patients' serum and that in porcine serum and liver extract indicates that the porcine L.D.H. is derived from the pig liver. This finding reflects damage to the pig liver cells sustained during porcine hepatectomy and subsequent perfusion. Possibly patients might develop immune reactions against porcine substances when these entered the circulation, especially if perfusion was repeated after an interval of some time.